A Reading of the Proverbs of Sheikh Mohammed Khal from the Perspective of Moral Psychology - Hamaghareb, Dr. Sazan Jawhar; Khalil, Dr. Sumaya Najib (Sulaimani Journal for Humanities, 2023)
Ethical behavior covers an important aspect of people's personalities and careers and is considered a key principle in evaluating an individual's image in society. In psychology, ethical behaviors are viewed as an individual's moral identity in society and are considered to improve an individual's image, ability to make sound decisions, eliminate anxiety and success. Proverbs as a literary text, which is born of a mental state and carries many concepts and moral values and anti-immoral values, can be analyzed within the framework of moral psychology and the most important moral behaviors can be identified. At the same time, the immoral tendencies and thoughts that are rejected by the beliefs and cultural traditions of the Kurdish people in general and by the superego of the Kurdish individual in particular are identified. This paper consists of two parts. The first part deals with the concepts and terms of moral psychology, the principles and advantages of this concept in psychology, and the importance of the value of moral behaviors and moral motives on personality psychologically. The second part is dedicated to reflecting the most important moral values reflected in Kurdish proverbs and is evaluated in a psychological, moral, cultural and value framework of Kurdish society.
Keywords: moral psychology; motivation; power of mind; ethics; proverbs